(untitled) (ModaPalavra e-periódico, 2023)
This article is an account of a non-formal pedagogical experience that proposed the reading of 3 images to a group of 5 people of different genders and ages. The analyzed images were chosen because they referred to the cover of the September 2018 issue of the American Vogue Magazine with Beyoncé. The intention was to investigate whether it would be possible to promote a discussion about fashion images and increase the perception of visual culture, through the exercise of image reading. The proposal was systematized in three pedagogical moments and the image reading was based on Oliveira (2006). As a result, the participants ́ view was deepened and meaningful discussions were initiated on models of femininity and the intertextual relations surrounding the theme of representations of Bahian women.